The Impacts Of Distributed Photovoltaic Generation On Power Distribution Networks Losses - Sa'adah, Daud; Aida Fazliana, Abdul Kadir; Gan, Chin Kim (Institute Of Electrical And Electronics Engineers Inc. (IEEE), 2016)
The maximum allowable penetration level of Photovoltaic-based distributed generation (PVDG) is one of the major concerns in power system. It gives significant impacts since PVDG might inject positive and negative effects to the distribution system. In this regard, this paper investigates the relationship between PVDG injections on distribution system and system losses. Three different IEEE test systems have been considered in this work, namely IEEE 13 bus, IEEE 30 bus and IEEE 69. Each test system consists of four simulation cases in order to determine the effect of PVDG on the systems losses under various penetration levels. PVDG is injected at different buses connected to different load values. The optimum penetration level is based on the system’s power losses. The penetration level must not exceed the maximum boundary in term of total losses for the systems to maintain its efficiency and reliability.